Psychotic experiences and psychological distress predict contemporaneous and future non-suicidal self-injury and suicide attempts in a sample of Australian school-based adolescents - Martin, G.; Thomas, H.; Andrews, T.; Hasking, Penelope; Scott, J. (Cambridge University Press, 2015)
Copyright © Cambridge University Press 2014. Background Recent cross-sectional studies have shown psychotic experiences (PEs) are associated with suicidal ideation and behaviours. We aimed to examine associations between psychotic experiences (including persistent PE), and contemporaneous and incident non-suicidal self-injury (NSSI) and suicide attempts. Method Participants were from an Australian longitudinal cohort of 1896 adolescents (12-17 years). NSSI and suicide attempts were measured using the Self-Harm Behaviour Questionnaire. Items from the Diagnostic Interview Schedule for Children were used to assess psychotic experiences, and the General Health Questionnaire-12 measured psychological distress. Results Adolescents both psychologically distressed and endorsing psychotic experiences had increased odds of contemporaneous and incident NSSI and attempted suicide. Psychotic experiences alone did not predict future risk. Persistent psychotic experiences were associated with increased risk of NSSI and suicide attempts. Conclusions Psychological distress with accompanying psychotic experiences and persistent psychotic experiences are important predictors of NSSI and suicide attempts. Screening these phenotypes in adolescents will assist in discerning those adolescents most at risk, providing opportunities for targeted suicide prevention strategies.